Rethinking Taxation in Latin America Reform and Challenges in Times of Uncertainty (Latin American Political Economy, 2018)
Jorge Atria is Researcher at Pontificia Universidad Católica de Chile and Adjunct Researcher at Centre for Social Conflict and Cohesion Studies (COES), Chile. Constantin Groll is Researcher at Freie Universität Berlin, Germany. Maria Fernanda Valdés is a program coordinator for the Friedrich Ebert Stiftung in Bogotá, Colombia. This study of taxation in Latin America takes a novel approach to the subject, using a framework that posits three dimensions for studying taxes-historical, relational, and transnational. The book argues that: first, taxation should be understood as a relational concept and tax systems as a function of a strategic nexus between the state and society; second, that any analysis of tax systems across Latin America needs to take historical legacies of national tax systems into account; and finally, that transnational phenomena have significant implications for tax regime dynamics in Latin America. The essays included provide diverse and representative insights for a new understanding of taxation in Latin America and highlight the bottlenecks to the development of sustainable tax systems in the region, exploring new links between academic research and policy-making.